Green H2O-Promoted Solvent-Free Synthesis of Enaminocarbonyl Compounds with High Stereoselectivity from Electron-Deficient Terminal Alkynes - Chen, Xiao Yun; Zhang, Luming; Tang, Yaonan; Yuan, Shuxia; Zhu, Baocheng; Chen, Guang; Cheng, Xiaofang (Synlett, 2020)
A green H2O-promoted solvent-free hydroamination of electron-deficient terminal alkynes with amines has been developed. All secondary amines, including aliphatic and aromatic amines, gave the corresponding (E)-enamines in good to excellent yields, whereas primary aromatic amines afforded Z-configured products in moderate yields. Propiolates, propyn-1-ones, propynamides, and 1-(ethynylsulfonyl)-4-methylbenzene were explored in this Michael addition.
Keywords: green chemistry; water catalysis; hydroamination; alkynes; enamines